Pengembangan Pelabuhan Perikanan “Tanjung Adikarto” di Kabupaten Kulonprogo dengan Pendekatan Arsitektur Ekologi - Agus Setyawan; Joko Santoso; Mufidah Mufidah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
In the context of carrying out fisheries activities, the Tanjung Adikarto Fishing Port does not fully meet the requirements as a Coastal Fishing Port (Type C). Complete facilities such as cold storage, shops, ship maintenance and fishing equipment, as well as places for handling and processing fishery products are still not available, while several other facilities also do not meet adequate standards. In this section, the author will describe the actual conditions of the facilities at Tanjung Adikarto Port and their comparison with the standard facilities that a Coastal Port (Type C) should have. This is the first step to evaluate what needs to be improved in order to increase the capacity and feasibility of the port to support more optimal fishing activities. Observations of the existing condition of the port have revealed several problems that need attention. Buildings that are damaged and uninhabitable are one of the main issues that need to be addressed immediately. The aim is not only to ensure port operations run optimally, but also to align port activities with environmental sustainability, so that their contribution to the community's economy can be realized in a sustainable manner.